2010
DOI: 10.1097/acm.0b013e3181ed38fc
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Four Approaches of Using Repeatersʼ MCAT Scores in Medical School Admissions to Predict USMLE Step 1 Total Scores

Abstract: Using the average score is the best approach for considering repeaters' MCAT scores in medical school admission decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…Data from the American Board of Internal Medicine (ABIM) and the American Board of Surgery have also demonstrated a positive association between scores on the primary certification and maintenance of certification (MOC) examinations [5]. This correlation is not limited to ABMS member board examinations because performance on the Medical College Admission Test scores strongly correlate with United States Medical Licensing Examination scores [11], and United States Medical Licensing Examination scores predict performance on ABMS member board in-training and certifying examinations [1,12,13]. In essence, this study confirms that good written test takers remain good written test takers over time.…”
Section: Discussionmentioning
confidence: 91%
“…Data from the American Board of Internal Medicine (ABIM) and the American Board of Surgery have also demonstrated a positive association between scores on the primary certification and maintenance of certification (MOC) examinations [5]. This correlation is not limited to ABMS member board examinations because performance on the Medical College Admission Test scores strongly correlate with United States Medical Licensing Examination scores [11], and United States Medical Licensing Examination scores predict performance on ABMS member board in-training and certifying examinations [1,12,13]. In essence, this study confirms that good written test takers remain good written test takers over time.…”
Section: Discussionmentioning
confidence: 91%
“…Step 1 performance, and therefore, they should be included in statistical analysis (Donnon et al, 2007;Zhao, 2010).…”
Section: Assessment Of Student Populationmentioning
confidence: 99%
“…Therefore, policies from other specialty programs, such as medical and law schools, are useful for comparison. These specialty programs incorporate various guidelines for multiple attempts of the MCAT and LSAT, which are consistent with the aforementioned polices used for general college admission (Dalessandro et al, 1999;Wightman, 1990;Zhao et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 88%
“…Patterson et al (2012) examined this issue in relation to the SAT and found that none of the methods undermined the predictive validity of the test. Currently, no consensus exists in the literature for the proper treatment of multiple scores, although using the average of all attempts is often recommended (Dalessandro & McLeod, 1999;Roszkowski & Spreat, 2016;Wightman, 1990;Zhao, Oppler, Dunleavy, & Kroopnick, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation